Perspective Of Business Culture And Work Ethos Japanese And Chinese Communities - Yessy Harun; Febi Nur Biduri (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2019)
The work culture and work ethic in the countries of East Asia are certainly different from other countries in the world, where the purpose of research is to know:1. Ojigi's influence in the success of Japanese business in Japan.2. Knowing the cultural perspective and work ethic of the Chinese community. This study uses a qualitative method of library research methods and questionnaire methods taken from several businessmen from Japan and China who are in Indonesia.